Feeding of Infants and Young Children in South Asia - Torlesse, Harriet (World Bank, Washington, DC, 2018)
Poor breastfeeding and complementary feeding practices predict child stunting and wasting in South Asia, suggesting that initiatives to end undernutrition in the region should focus on improving the diets of young children. This review of the literature finds that South Asia has made relatively good progress in improving breastfeeding practices compared with other regions, but the lack of diversity in complementary foods and low frequency of feeding continue to be problems. Children who are most at risk of experiencing poor feeding include those who are born small, have younger mothers, and live in poorer households or in communities with less access to, or lower uptake of, primary health services. Initiatives to improve feeding practices have not produced substantial improvement, particularly in complementary feeding, because such efforts have lacked the coverage, intensity, comprehensiveness, and continuity needed. Policy, legal, and program actions to protect, promote, and support recommended feeding practices should be informed by situation analyses and formative research on context-specific drivers of poor practices. The actions should involve multiple sectors and stakeholders, including governments, the private sector, communities, and households.